Judicial Ingroup Bias in the Shadow of Terrorism * - Shayo, Moses; Zussman, Asaf (Quarterly Journal of Economics, 2011)
We study ingroup bias —the preferential treatment of members of one’s group —in naturally occurring data, where economically significant allocation decisions are made under a strong non-discriminatory norm. Data come from Israeli small claims courts during 2000-04, where the assignment of a case to an Arab or Jewish judge is essentially random. We find robust evidence for judicial ingroup bias. Furthermore, this bias increases with terrorism intensity in the vicinity of the court in the year preceding the ruling. The results are consistent with theory and lab evidence according to which salience of group membership enhances social identification.